2020
DOI: 10.1097/fjc.0000000000000899
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Renal Denervation on Cardiac Function and Inflammatory Factors in Heart Failure After Myocardial Infarction

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Compared with RDN-1d + AMI group, NGF decreased more significantly in RDN-2 W + AMI group, suggesting that RDN may not change the expression of Th and NGF immediately, with a hysteresis. Wanying Jiang et al [ 31 ] found that RDN significantly reduced the expression of Th and connexin 43 in the infarct zone of AMI rats compared with metoprolol, which suggests that RDN may not only decrease myocardial sympathetic activity in AMI via NE/β receptor signaling pathway, but may also be associated with the inhibition of inflammation, the RASS system [ 27 , 32 ].However, the mechanism by which RDN weakens the sympathetic activity of myocardial tissue is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with RDN-1d + AMI group, NGF decreased more significantly in RDN-2 W + AMI group, suggesting that RDN may not change the expression of Th and NGF immediately, with a hysteresis. Wanying Jiang et al [ 31 ] found that RDN significantly reduced the expression of Th and connexin 43 in the infarct zone of AMI rats compared with metoprolol, which suggests that RDN may not only decrease myocardial sympathetic activity in AMI via NE/β receptor signaling pathway, but may also be associated with the inhibition of inflammation, the RASS system [ 27 , 32 ].However, the mechanism by which RDN weakens the sympathetic activity of myocardial tissue is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, RSD significantly reduced LV end-diastolic volume and improved LVEF [ 218 ]. Cardioprotection by RSD was also reported in a canine HF model induced by intra-coronary injection with ethanol to induce embolization [ 219 ]. At four weeks after coronary embolism, dogs with RSD showed significantly attenuated LV dilatation and better preservation of LV function.…”
Section: Recent Research Progressmentioning
confidence: 95%
“…At four weeks after coronary embolism, dogs with RSD showed significantly attenuated LV dilatation and better preservation of LV function. Interestingly, expression in the myocardium and hypothalamus of several inflammatory factors, like IL-6, MCP-1 (monocyte chemoattractant protein-1), tumour necrosis factor-α (TNFα) and NF-κB (nuclear factor κ-light chain-enhancer of activated B cells), was significantly lower in RSD relative to sham-procedure controlled HF animals, indicating attenuated cardiac and central inflammatory signaling by RSD [ 219 ]. Similar beneficial effects by RSD was also reported in a very recent canine study with HF induced by rapid ventricular pacing [ 220 ].…”
Section: Recent Research Progressmentioning
confidence: 99%